The Effect of Financial Literacy, Financial Experience, and Lifestyle on The Personal Financial Management Ability of Generation Z Students at The Faculty of Economics, University of Muhammadiyah Sukabumi - Nasywa, Salwa Aftar; Kartini, Tina; Nurodin, Idang (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the influence of financial literacy, financial experience, and lifestyle on the personal financial management of Generation Z students at the Faculty of Economics, Muhammadiyah University of Sukabumi. The research employed a quantitative approach using a survey of 100 respondents. Regression results indicate that financial literacy and financial experience have a positive and significant effect on financial management, while lifestyle shows a negative and significant influence. Simultaneously, all three variables significantly contribute to students’ ability to manage their finances. These findings highlight the importance of sufficient financial literacy and experience, along with lifestyle control, in shaping healthy financial behavior among Generation Z.